Decoupling study of volatile–char interaction during coal/biomass co-gasification based on a two-stage fixed bed reactor: Insight into the role of O-containing compound species. (16th January 2023) - Ma, Meng; Bai, Yonghui; Wei, Juntao; Song, Xudong; Lv, Peng; Wang, Jiaofei; Su, Weiguang; Xiong, Qingang; Yu, Guangsuo
Highlights: Volatile–char interaction inhibited the occurrence of deacidification and deketoization reactions. PAHs occupied the active site was the main cause for coal char deactivation. Phenolic hydroxyl group were more favorable for diaryl ether dissociation showing the strongest inhibition. Inhibition behavior on reactivity follows the order: Phenolic hydroxyl > Carboxyl > Aldehyde > Ether group. Abstract: Volatile–char interaction is a significant contributor to low equipment reliability and energy efficiency of gasifier equipment. In this work, volatile–char interaction during the coal/biomass co-gasification process is explored based on a two-stage fixed bed reactor decoupling, the variations in liquid–gas-solid three-phase product composition and reactivity are discussed in detail, and the contributing behaviors of different O-containing compounds to coal char deactivation were analyzed. The essence of volatile–char interaction is the process of deoxidation, dehydrogenation and ring-opening repolymerization of tar compounds, and inhibits decarboxylation and deketoization. The PAHs generated by the polymerization of O-containing compounds occupy the active sites and is the main reason for coal char deactivation during gasification. And the functional groups are phenolic hydroxyl, carboxyl, aldehyde and ether in the order of action strength. This study provides the potential for directional regulation of product distribution to reduce interaction intensity, which is helpful for gasifier design and operation optimization.